Thermo-physical properties of concrete exposed to high temperature - Kizilkanat, Ahmet B.; Yuzer, Nabi; Kabay, Nihat (ELSEVIER SCI LTD, 2013)
The processes of heat penetration into a concrete mass are extremely important. Under high temperature effect, chemical composition and physical structure of concrete changes. These changes are primarily observed at the cement paste and then at the aggregates as well. In this paper, the effect of high temperature on thermal conductivity and moisture resistance factor of concrete with different types of pozzolans and aggregates is investigated. These parameters are analyzed in eight different types of concrete mixes depending on the presence of silica fume, granulated blast furnace slag and fly ash with siliceous and calcareous aggregates. In the scope of this study, simplified formulas of second order with high correlation factors have been derived that give thermal conductivity and moisture resistance factor as a function of temperature in the range of 0-600 degrees C for the concrete series separately. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: High temperature; Aggregate; Pozzolan; Concrete; Thermal conductivity; Moisture resistance factor; FLY-ASH; STRENGTH; CONDUCTIVITY; Construction & Building Technology; Engineering; Materials Science